"Why did nobody tell us?" Business journalism and the financial crisis - Tambini, Damian (Henry Stewart Talks, 2010)
Role of business and financial journalism in providing public information on the financial crisis, Ethical and regulatory framework within which business journalism operates, Criticism of business journalism, Rights and responsibilities of journalists, The public interest/watchdog role of business and financial journalists